Methabolic and immune aspects of cardiovascular disease in car drivers - M. A. Umetov; A. M. Inarokova; S. A. Khadzegova; E. K. Vok; Z. M. Kodzoev (Российский кардиологический журнал, 2004)
Immune and hormonal status, together with metabolic syndrome (MS) clinic, were examined in 207 males - car drivers (CD) suffering arterial hypertension (AH), coronary heart disease (CHD) or their combination (mean age 47.7 ± 5. 1). In CD with MS, prevalence of subclinical hypothyrosis (41.5 %) was almost twice as high as in healthy individuals (22.2 %). Besides, among the former, increased levels of leptin, fibrinogen, ACTH, Cortisol, and decreased T-cell immunity were more prevalent than in CD with isolated AH, and in healthy people. Positive correlation between leptin level and increased body weight, TTG, insulin and triglycerides levels was observed.